The Impact of Artificial Intelligence On Higher Learning Institutions - Bongs Lainjo; Hanan Tsmouche (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Artificial intelligence applications in education have attracted the attention of multiple parties, including scholars, educators, governments, and researchers. The article aims to conduct a comprehensive and inclusive review of the proliferation and impact of Artificial intelligence on Higher Learning. Chronologically, the focus has been artificial intelligence applications in higher learning since the early 1950s. There needs to be more literature regarding the adoption of AI in higher education, resulting in a substantial limitation of this article. This article also discusses the role of cyber security in adopting AI in higher education. The authors have also discussed various applications of AI in higher education and the challenges. This article presents some recommendations. More research is needed as the recommendations are based on a limited number of scholarly articles. A Georgia State University case study conducted in 2015 substantiates AI adoption's benefits in higher education.